2020
DOI: 10.3390/plants9030318
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regeneration Potential of White Lupin (Lupinus albus) from Cotyledonary Nodes

Abstract: The tissue culture regeneration system of Lupinus albus has always been considered as recalcitrant material due to its genotype-dependent response and low regeneration efficiency that hamper the use of genetic engineering. Establishment of repeatable plant regeneration protocol is a prerequisite tool for successful application of genetic engineering. This aim of this study was to develop standardized, efficient protocol for successful shoot induction from cotyledonary node of white lupin. In this study, 5 day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
(80 reference statements)
2
11
0
6
Order By: Relevance
“…The quality of the root induction is affected by the composition and concentration of the media, most species require auxin to induce rooting and shoot promotion 30 , but the root induction rate was decreased with increasing concentration of IAA 31 . Some research showed that IBA was found to be more effective in rooting induction compared to NAA and IAA 25,32 .…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the root induction is affected by the composition and concentration of the media, most species require auxin to induce rooting and shoot promotion 30 , but the root induction rate was decreased with increasing concentration of IAA 31 . Some research showed that IBA was found to be more effective in rooting induction compared to NAA and IAA 25,32 .…”
Section: Resultsmentioning
confidence: 99%
“…al., 2017;Sojková et al, 2016) использован газообразный хлор как стерилизующий агент. Другие авторы использовали этанол: 70% (Soto et al, 2013;Kantayos, Bae, 2019b;Varlamova et al, 2018) и 75% (Aslam et al, 2020), 3-процентную перекись водорода (Zhumagulova, 2014), твин-20 (Raza et al, 2020) и концентрированную соляную кислоту (Mangena, Mokwala, 2019). Длительность стерилизации составляла от 15 минут до 20 часов, в отдельных случаях достигала 48 часов.…”
Section: фактор инициации культуры In Vitrounclassified
“…Практически во всех работах по изучению регенерационной способности сои (Sojková et al, 2016;Raza et al, 2019;Aslam et al, 2020) авторы использовали питательную среду на основе среды Мурасиге-Скуга (МС) (Murashige, Skoog, 1962) (табл. 2).…”
Section: влияние состава питательной среды: минеральная основа и регуляторы ростаunclassified
See 1 more Smart Citation
“…White lupin ( Lupinus albus ) is an economically important legume crop belonging to the family Fabaceae due to its high nutritious value, high protein and low oil contents [ 22 ]. It gained a lot of research attention due to its significant role in improving nutrient mobilization, soil exploration and fertility, and nitrogen-fixing ability [ 23 ].…”
Section: Introductionmentioning
confidence: 99%